Radical Remembering: Contaminating Memory in the Works of Martin Lynch - Maguire, Tom (Archīum Ateneo, 2024)
Martin Lynch has been prominent in the practice of community theatre in Northern Ireland through works like The Stone Chair and The Wedding Community Play and his role as founding Chair of Belfast’s Community Arts Forum. This essay argues, however, that in his work as a playwright engaged in staging the remembered histories of Belfast’s working class, it is possible to regard him as a radical playwright. Locating Lynch in the tradition of John McGrath’s popular theatre allows his work to be seen as both recovering working class experience and, crucially, probing mythologies that have justified and perpetuated political violence. The paper is focused particularly on two of Lynch’s most recent works: Holding Hands at Paschendale (2006) and The Long Kesh Chronicles (2009).